Kaizen implementation to reduce dimensional defect in the welding process of Fender D155A-6R at PT Arkha Jayanti Persada - I.G.B.E.P. Yana; P.D. Setyawan; I.M. Suartika; A. Rachmalia; M.M. Aziz (Dinamika Teknik Mesin, 2025)
Kaizen is a concept of continuous improvement that emphasizes quality enhancement and efficiency in production processes. In this study, the Kaizen approach was applied to address dimensional defects in the welding process of the Fender D155A-6R component at PT. Arkha Jayanti Persada. The component, which was previously imported from Japan, is currently being tested through local production trials. Initial inspection indicated that 11 of 33 measurement points were out of tolerance, most of which were linked to welding activities. To analyze the problem, the PDCA (Plan, Do, Check, Act) cycle was employed. The investigation revealed several contributing factors: the absence of a locator to secure parts during welding, insufficient reinforcement that caused deformation, and the lack of a standardized welding procedure for operators. Corrective measures were then introduced, including the installation of a locator, additional reinforcements, and the establishment of a formal welding procedure. After two PDCA cycles, the dimensional issues were successfully resolved. The findings indicate that applying Kaizen through PDCA led to significant improvements in dimensional accuracy and product quality.